MORDEDURAS HUMANA E ANIMAL - Oliveira, Ana Maria de; Vale Serra, Maria Helena Vieira Sá; Vieira, Maria Regina Dâmaso (Revista de Patologia Tropical / Journal of Tropical Pathology, 2007)
MORDEDURAS HUMANA E ANIMAL